Towards game engagement: usability evaluation of digital Malaysian traditional games - Abu Bakar, Nur Azzah (Universiti Teknikal Malaysia Melaka, 2016)
Sustainable engagement in digital traditional games can preserve country’s cultural heritage. However, despite such importance, digital traditional games are far less popular than the digital contemporary games.This study investigates one dimension of user engagement by empirically evaluate their usability aspects. Three digital versions of Malaysian traditional games namely Dam Haji, Congkak and Gasing-X were chosen.Literature suggested that usability problems may affect user engagement in the game. In contemporary games, usability is one of the attributes that promotes attractiveness which later leads to engagement.To date, little is known whether usability is also deemed critical for users to become engaged to traditional games. Usability helps in verifying the requirements, successes and functionality of the games which are missing.Evaluation involved 50 respondents who are IT and domain experts, using the instrument that was adopted from Jakob Nielsen’s usability evaluation principles. The instrument consists of 17 heuristic component protocols based on interface design.The results revealed several usability issues with current digital Malaysian traditional games including aesthetic and minimalist design, error prevention, help and documentation and assessment, which should be given serious attention in the development of future digital Malaysian traditional games.